Answer:
![D: y= -5x+12](https://tex.z-dn.net/?f=D%3A%20y%3D%20-5x%2B12)
Step-by-step explanation:
Since the slope is -5 is either C or D. Let's replace
in either to see what we get.
C:
Nope.
D:
Good!
Answer:
6
Step-by-step explanation:
10/5 ×/3 multiply 10×3 and than divide by 5
or another way start with multiplying 5 and n equaling 5n=
than 10× 3= 30 so you're left with 5n=30 divied 30 by 5 equalling 6
so x=6
we are given
![f(x)=x^2-4x+5](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2-4x%2B5)
Since, we have to find inverse of this function
step-1: we set f(x)=y
![y=x^2-4x+5](https://tex.z-dn.net/?f=y%3Dx%5E2-4x%2B5)
step-2: switch x and y
![x=y^2-4y+5](https://tex.z-dn.net/?f=x%3Dy%5E2-4y%2B5)
step-3: Solve for y
![y^2-4y+(5-x)=0](https://tex.z-dn.net/?f=y%5E2-4y%2B%285-x%29%3D0)
now, we can use quadratic formula
![y=\frac{4+\sqrt{4^2-4(5-x)} }{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B4%2B%5Csqrt%7B4%5E2-4%285-x%29%7D%20%7D%7B2%7D)
![f^{-1}(x)=\sqrt{x-1}+2](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Csqrt%7Bx-1%7D%2B2)
or
..............Answer
The first expression can be simplified by combining like terms.
First, the terms "4b" and "-3b" can be combined to form "b"
Then, the terms "-7" and "9" can be combined to form "2"
Finally, we simply put these two final terms together, to form "b+2"
Hence, 4b-7-3b+9 is equal to be + 2.
Hope this helps!
Answer:
12
Step-by-step explanation: